2007
DOI: 10.1007/s00425-007-0648-2
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis cax3 mutants display altered salt tolerance, pH sensitivity and reduced plasma membrane H+-ATPase activity

Abstract: Perturbing CAX1, an Arabidopsis vacuolar H+/Ca2+ antiporter, and the related vacuolar transporter CAX3, has been previously shown to cause severe growth defects; however, the specific function of CAX3 has remained elusive. Here, we describe plant phenotypes that are shared among cax1 and cax3 including an increased sensitivity to both abscisic acid (ABA) and sugar during germination, and an increased tolerance to ethylene during early seedling development. We have also identified phenotypes unique to cax3, nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
89
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 62 publications
5
89
1
Order By: Relevance
“…2005), and evidence suggests altered regulation of proton pumps when CAX expression is deregulated (Zhao et al . 2008; Conn et al . 2011).…”
Section: The Cax Transporters In Abiotic Stress Signallingmentioning
confidence: 99%
“…2005), and evidence suggests altered regulation of proton pumps when CAX expression is deregulated (Zhao et al . 2008; Conn et al . 2011).…”
Section: The Cax Transporters In Abiotic Stress Signallingmentioning
confidence: 99%
“…Non-selective cation channels (NSCCs) can also mediate Na + fluxes (Zhao et al 2011), although their molecular/genetic characterization is currently unknown. At the tonoplast, Na + sequestration is linked to cation exchangers (CAX and NHX; Zhao et al 2008;Apse et al 2003) and vacuolar channels (SV and FV;Ivashikina and Hedrich 2005;Isayenkov et al 2010). SV channels are also blocked by luminal Na + (Ivashikina and Hedrich 2005).…”
Section: Sodium As a Nutrientmentioning
confidence: 99%
“…At the tonoplast, vacuolar sequestration of Na + has been attributed to the function of Na + /H + exchangers (NHX; Blumwald and Poole 1985;Apse et al 1999Apse et al , 2003 and both slow-vacuolar (SV) (Hedrich and Neher 1987;Schönknecht et al 2002;Ivashikina and Hedrich 2005) and fast-vacuolar (FV) channels (Isayenkov et al 2010). It has further been suggested that members of the cation exchanger (CAX) family could transport Na + (Luo et al 2005; see also Zhao et al 2008), but, again, none of these candidates is a part of current models of guard cell function. No leading reviews or textbook treatises on stomatal guard cell function have incorporated these flexibilities and, instead, they make the case for very specific, and central, engagement of K + channels/transporters as integrated into a tightly orchestrated cascade of events, involving hormone binding, Ca 2+ fluxes, and membrane potential activation of K + fluxes (Schroeder et al 2001).…”
Section: Sodium As a Nutrientmentioning
confidence: 99%
“…However, only CAX1 to CAX4 have been functionally characterized to possess a vacuolar Ca 2+ /H + exchange activity. Whereas CAX1 and CAX3 mediated specifically Ca 2+ transport (Hirschi, 1999;Catala et al, 2003;Cheng et al, 2003;Mei et al, 2007;Zhao et al, 2008), CAX2 and CAX4 were documented to have high transport and selectivity for cadmium ions (Cd 2+ ) over Ca 2+ in tonoplast vesicles (Hirschi et al, 2000;Cheng et al, 2002;Pittman et al, 2004;Koren'kov et al, 2007).…”
mentioning
confidence: 99%
“…Conversely, transgenic tobacco plants overexpressing CAX1 were hypersensitive to ion imbalance and cold shock and exhibited Ca 2+ -deficient symptoms in spite of increased accumulation of Ca 2+ (Hirschi, 1999). Loss-offunction of CAX3, a close homolog of CAX1, increased the sensitivity to salt stress, lithium, and low pH (Zhao et al, 2008). While cax1 and cax3 single mutants displayed subtle phenotypes, the cax1/cax3 double mutant showed stunted growth with chlorosis on the leaf tips and a drastic reduction in silique size and seed numbers (Cheng et al, 2005).…”
mentioning
confidence: 99%